Unveiling patterns in promoting Romania's Nature Parks as Tourist Destinations: Insights into traveler preferences through social media - Vasile JITARIU; Oana-Letitia CIUBOTARIU; Andrei-Cosmin OLARIU; Ana-Maria ANASTASIEI (Present Environment and Sustainable Development)
In the context of tourism development and technological evolution, analyzing the virtual framework for information distribution plays a crucial role in understanding the promotional trends of responsible institutions and the range of interests of social media users regarding tourism in protected areas. The purpose of this study is not the anticipation of tourist arrivals in a Nature Park based on the number of likes, shares, or comments, but to examine the Facebook image of some important natural protected areas and the tourist preferences in matter of nature social media. The general impression is the fact that the most popular Nature Parks have the most posts, in special posts that contain at least one photo or one video. The exclusive text posts were not as appreciated by the public as the video/photo posts. Another classification of Facebook posts was due to the main subject in the post: animals, plants, food, accommodation, human activity, or landscape; this revealed that animal biodiversity and human activity are the most promoted topics.